Enhanced Interfacial Properties of Carbon Nanomaterial–Coated Glass Fiber–Reinforced Epoxy Composite: A Molecular Dynamics Study - Song, You; Lan, Zhenbo; Deng, Jiangang; Xu, Zhuolin; Nie, Yu; Chen, Yanming; Yang, Bing; Hao, Huali (Frontiers in Materials, 2022)
The weak interfacial adhesion has significantly affected the durability, long-term reliability, and performance of glass fiber reinforced epoxy composites. The incorporation of graphene and carbon nanotubes coated on the glass fiber can have a positive effect on the strength, toughness, as well as thermal insulation performance. However, the strengthening mechanism of carbon nanomaterials coating on the interfacial adhesion between glass fiber and epoxy has not been fully explored. In this work, the effect of graphene and single-walled carbon nanotubes (SWCNTs) on the interfacial properties of the glass fiber reinforced epoxy has been investigated at atomistic scale. The graphene and SWCNTs are sandwiched between epoxy and silica to study the debonding behavior of the sandwiched structures. It is found that the interfacial energy is significantly improved with the incorporation of graphene and SWCNTs between epoxy and silica, causing an obvious improvement in adhesion stress for graphene coating and in debonding displacement for SWCNTs coating. Compared with the epoxy/silica without coatings where the silica and epoxy detach from the contact surface, the sandwiched structures display different failure modes. The sandwiched structure with graphene coating fails at the epoxy matrix close to the interface exhibiting a cohesive failure mode because of the relatively stronger interfacial interactions. The structures with SWCNTs fail at the interface between silica and SWCNTs representing an adhesive failure mode due to the interlocking between SWCNTs and polymer chains. This work provides a theoretical guideline to optimize the interface adhesion of coated glass fiber reinforced epoxy via structure design and surface modification of coating materials.